Minat Memilih Profesi MedRep Ditinjau dari Persepsi dan Citra Profesi - Mardewi, Criana; Riady, Hanes (Jurnal Ilmu Manajemen, 2015)
This study examines students’ perceptions and brand image of MedRep as the predictors of purchase intentions for the MedRep profession. To examine the proposed research model, 100 samples are collected. Multiple regressions are used to test the hypotheses. There are mixed results in relation to the tested relationships. Brand image have a significant impact on student purchase intention for the MedRep profession. Surprisingly, analysis using the student sample indicated that students’ perception has no significant impact on student purchase intention for the MedRep profession.